Thermophilic and mesophilic temperature phase anaerobic co-digestion (TPAcD) compared with single-stage co-digestion of sewage sludge and sugar beet pulp lixiviation. (October 2016) - Montañés Alonso, Rocío; Solera del Río, Rosario; Pérez García, Montserrat
Abstract: The performance of temperature phase anaerobic co-digestion (TPAcD) for sewage sludge and sugar beet pulp lixiviation (using the process of exchanging the digesting substrate between spatially separated thermophilic and mesophilic digesters) was tested and compared to both single-stage mesophilic and thermophilic anaerobic co-digestion. Two Hydraulic Retention Times (HRT) were studied in the thermophilic stage of anaerobic digestion in two temperature phases, maintaining the optimum time of the mesophilic stage at 10 days, obtained as such in single-stage anaerobic co-digestion. In this way, we obtained the advantages of both temperature regimes. Volatile solids removal efficiency from the TPAcD system depended on the sludge exchange rate, but fell within the 72.6–64.6% range. This was higher than the value of 46.8% obtained with single-stage thermophilic digestion and that of 40.5% obtained with mesophilic digestion. The specific methane yield was 424–468 ml CH4 per gram of volatile solids removed, similar to that of single-stage mesophilic anaerobic digestion. The increase in microbial activity inside the reactor was directly proportional to the organic loading rate (OLR) (or inversely proportional to the HRT) and inversely proportional to the size of the microbial population in single-stage anaerobic co-digestion systems. Highlights: Two-phase anaerobic co-digestion (TPAD) showed good performance in effluent quality. Different organic loading rates and hydraulic retention times (HRT) were carried out. The performance of TPAcD was dependent on the HRT of the thermophilic digester. Advantages of mesophilic and thermophilic anaerobic co-digestion have been obtained. The increase in microbial activity is proportional to the organic loading rate.